Pengaruh Struktur Modal Dan Profitabilitas Terhadap Harga Saham : Ukuran Perusahaan Sebagai Moderasi - Luluk Fiya Afiati; Utami Puji Lestari (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
The purpose of this study is to investigate and evaluate the effect of profitability and capital structure on stock prices, as well as the moderating effect of firm size. The study population consisted of 91 energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2022 and 2024. After using a purposive sampling technique, a final sample of 58 companies with 174 observations was obtained. A Fixed Effects Model (FEM), estimated using the Estimated Generalized Least Squares (EGLS) approach, was used in panel data regression analysis. The results of the hypothesis testing indicate that capital structure significantly and negatively influences stock prices. Conversely, profitability has no significant impact on stock prices. In terms of moderation, the relationship between capital structure and stock prices is significantly strengthened by firm size; however, the relationship between profitability and stock prices is not significantly moderated. Specifically, this study reduces information asymmetry in the capital market, advancing the theoretical development of signaling theory and the financial management literature.